2001
DOI: 10.1002/ajh.1070
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability states in upper‐extremity deep venous thrombosis

Abstract: Deep venous thrombosis of the upper extremity (DVTUE) is a rare thrombotic disorder that may occur spontaneously but is most often related to predisposing factors, such as an indwelling central venous catheter, malignancy, or exercise. The role of coagulation disorders, i.e., a hypercoagulable state in the pathogenesis of DVTUE is not well known. We have evaluated both genetic and acquired thrombophilia parameters in consecutive patients with DVTUE. A hypercoagulable state was found in 32% of the patients. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 16 publications
(20 reference statements)
2
44
0
5
Order By: Relevance
“…He´ron et al [7] also reported a high prevalence of hypercoagulable status in a population of patients with idiopathic UEDVT compared to those with effort-related UEDVT [42% (13/31) vs. 15% (3/20)]. Leebeek et al [21] recently found thrombophilic defects in 32% of their population with UEDVT and the most frequently found coagulation abnormality was the presence of antiphospholipid antibodies (27%). A recent publication documented the prothrombin G20210A mutation in 12.5% of patients with primary UEDVT and increased thrombotic risk in fertile women using oral contraceptives [22].…”
Section: Discussionmentioning
confidence: 95%
“…He´ron et al [7] also reported a high prevalence of hypercoagulable status in a population of patients with idiopathic UEDVT compared to those with effort-related UEDVT [42% (13/31) vs. 15% (3/20)]. Leebeek et al [21] recently found thrombophilic defects in 32% of their population with UEDVT and the most frequently found coagulation abnormality was the presence of antiphospholipid antibodies (27%). A recent publication documented the prothrombin G20210A mutation in 12.5% of patients with primary UEDVT and increased thrombotic risk in fertile women using oral contraceptives [22].…”
Section: Discussionmentioning
confidence: 95%
“…However, one study reported that low antithrombin III levels were associated with a greater risk for thrombosis [42]. Another study found that 32% of patients who had CVC thromboses had diagnoses of a hypercoagulable state; most had elevated anticardiolipin antibody levels, but there was no greater incidence of prothrombin 20210A mutation, Factor V Leiden, protein C deficiency, or protein S deficiency [62]. In a study in children, however, 63% of those with CVC thromboses did have an inherited risk factor, most of whom were compound heterozygotes [36].…”
Section: Patientmentioning
confidence: 99%
“…Whether thrombophilia due to deficiencies of the natural anticoagulant proteins antithrombin, protein C, and protein S; gain-of-function mutations in coagulation factor V and the prothrombin gene; or the metabolic abnormality hyperhomocysteinemia is associated with an increased risk of primary upper-extremity DVT remains a matter of debate. 2,[5][6][7][8][9][10][11] In addition, data on oral contraceptives as risk factor for primary upper-extremity DVT are scanty and controversial, 2,5,[7][8][9]11 whereas their role in lower-limb DVT 12 and cerebral vein thrombosis 13 is well established. Moreover, the rate of recurrence of upper-extremity DVT is unknown.…”
mentioning
confidence: 99%